Prevalence and Risk Factors of Exposure to COVID-19 Pandemic among Health Care Workers in Babylon, Iraq - Makki Hasan Shraifat; Foued Ben Haj Slama (Medical Journal of Babylon)
Background:COVID-19 is an extremely infectious disease. Health care workers (HCWs) are exposed to high occupational risk because of Coronavirus. Objectives:To study the prevalence and risk factors of exposure to COVID-19 among HCWs. Materials and Methods:The study design was cross-sectional and consisted of 527 participants of HCWs, Data was collected through direct interviews by using simple Random Sampling) technique, the questionnaire format was built exclusively by the researchers for this purpose and consisted of four axes which included socio-demographic variables, COVID-19 prevalence, vaccination status, and risk factors. Furthermore; Laboratory examinations were used in this study to detect newly infected cases of HCWs, we screened HCWs for SARS-CoV-2 via RT-PCR. The study period started from October 2, 2022 until May 30, 2023. This study was conducted at Babylon Health Directorate, Babylon governorate. Results:The findings indicate that a majority of HCWs participating in this study were in the age group 26–30 years 146 (27.7%), and predominantly females 302 (57.3%), 344 (65.3%) were residents in urban regions, with 228 (43.3%) holding technical diploma degree and nursing professionals makeup 201 (38.1%) of occupational titles, and most of them were working in emergency units 107 (20.3%). The results registered 352 (66.8%) of HCWs were infected previously with COVID-19, and 64 (12.1%) new infected cases diagnosed by RT-PCR, largely among paramedical staff 40 (20.3%), and a highly recorded at Al-Hashimiyah health sector 26 (11.9%). Data analysis reveals that a significant association between infection and some risk variables regards participants who visited epidemiological units, and those who visited physician clinics during the pandemic. Results suggest a significant association between not being vaccinated and COVID-19 infection. Additionally, the participants with chronic diseases were more likely to be infected compared to those without chronic diseases (P < 0.001). Conclusions:The study concluded that COVID-19 was prevalent among HCWs and significantly associated with some health and occupational risk factors.